Kill Rate and Evaluation of Ex Vivo PK/PD Integration of Cefquinome Against Actinobacillus pleuropneumoniae - Zhang, Longfei; Xie, Hongbing; Wang, Hongjuan; Ding, Huanzhong; Zhang, Gaiping; Hu, Jianhe (Frontiers in Veterinary Science, 2021)
We wished to study the detailed and precise antibacterial activity of cefquinome against Actinobacillus pleuropneumoniae (AP) in in vitro and ex vivo. We determined the kill rate in broth and analyzed the relationship between pharmacokinetic/pharmacodynamic (PK/PD) parameters and antibacterial effect in the serum and tissue cage fluid (TCF) of piglets. Cefquinome exhibited time-dependent antibacterial activity against AP according to the kill rate. The maximum kill rate was 0.48 Log10 CFU/mL/h at 0 h to 9 h in broth. In an ex vivo PK/PD study, the maximum concentration (Cmax), time to needed to reach the maximum concentration (Tmax), elimination half-life (T1/2β), and area under the concentration-time curve (AUCinfinity) were 5.65 μg/mL, 0.58 h, 2.24 h, and 18.48 μg·h/mL in serum and 1.13 μg/mL, 2.60 h, 12.22 h, and 20.83 μg·h/mL in TCF, respectively. The values of area under the curve during 24 h/minimum inhibitory concentration (AUC24h/MIC) for bacteriostatic, bactericidal, and bacterial-eradication effects were 18.94, 246.8, and 1013.23 h in serum and 4.20, 65.81 and 391.35 h in TCF, respectively. Our findings provide a valuable basis for optimization of dosage regimens when applying cefquinome to treat AP infection.